1994
DOI: 10.1016/0741-5214(94)90290-9
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of duplex criteria to assess significant carotid stenosis with special reference to reports from the North American Symptomatic Carotid Endarterectomy Trial and the European Carotid Surgery Trial

Abstract: The accuracy of duplex studies compared with angiography in the assessment of extracranial vascular disease depends on the method of angiographic determination of carotid stenosis. Vascular laboratories should validate the duplex criteria they use against a standard method of angiographic assessment of carotid artery stenosis, with special reference to the recently reported studies noting the significance of a stenosis greater than 70% in patients with symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
63
2
5

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(73 citation statements)
references
References 18 publications
0
63
2
5
Order By: Relevance
“…This threshold is similar compared with the study of Heijenbrok-Kal et al [27] where an optimal threshold value of 220 cm/s was found, or compared with the study of Grant et al [28] where the proposed threshold was 230 cm/s. Yet, our cut-off value is lower compared to that proposed by Moneta et al (325 cm/s) [29] , by Neale et al (270 cm/s) [30] and Saba et al (283 cm/s) [31] . Given the heterogeneity of these findings, it seems sensible that clinicians involved in the diagnosis and management of carotid artery disease use with caution hemodynamic criteria.…”
Section: Discussioncontrasting
confidence: 48%
“…This threshold is similar compared with the study of Heijenbrok-Kal et al [27] where an optimal threshold value of 220 cm/s was found, or compared with the study of Grant et al [28] where the proposed threshold was 230 cm/s. Yet, our cut-off value is lower compared to that proposed by Moneta et al (325 cm/s) [29] , by Neale et al (270 cm/s) [30] and Saba et al (283 cm/s) [31] . Given the heterogeneity of these findings, it seems sensible that clinicians involved in the diagnosis and management of carotid artery disease use with caution hemodynamic criteria.…”
Section: Discussioncontrasting
confidence: 48%
“…[7][8][9] This argument is based on the relative accuracy of Doppler ultrasound in previous studies. 5,6,[12][13][14][15] Dawson et al 5 prospectively studied 103 patients with 111 carotid stenoses with duplex scanning and conventional angiography. Carotid duplex studies were performed at vascular laboratories at 2 institutions.…”
Section: Discussionmentioning
confidence: 99%
“…So far, ultrasound Doppler examination has become well established for assessment of the lumen reduction caused by the carotid plaque [12], [26], [28], and the method has in some institutions supplanted arteriography even when carotid endarterectomy is planned. [16] However, during the last decade an increasing number of reports have indicated that Bmode ultrasound images of the carotid plaque reveal features (echogenicity and structure) related to the presence of brain infarcts on computed tomography images [17] and to the risk of developing new neurological symptoms [2], [6], [20], [22], [25], [32], [38].…”
mentioning
confidence: 99%